Identifying panaxynol, a natural activator of nuclear factor erythroid-2 related factor 2 (Nrf2) from American ginseng as a suppressor of inflamed macrophage-induced cardiomyocyte hypertrophy. (20th June 2015) - Qu, Chen; Li, Bin; Lai, Yimu; Li, Hechu; Windust, Anthony; Hofseth, Lorne J.; Nagarkatti, Mitzi; Nagarkatti, Prakash; Wang, Xing Li; Tang, Dongqi; Janicki, Joseph S.; Tian, Xingsong; et al.
Abstract: Ethnopharmacological relevance: American ginseng is capable of ameliorating cardiac dysfunction and activating Nrf2, a master regulator of antioxidant defense, in the heart. This study was designed to isolate compounds from American ginseng and to determine those responsible for the Nrf2-mediated resolution of inflamed macrophage-induced cardiomyocyte hypertrophy. Materials and methods: A standardized crude extract of American ginseng was supplied by the National Research Council of Canada, Institute for National Measurement Standards. A bioassay-based fractionization of American ginseng was performed to identify the putative substances which could activate Nrf2-mediated suppression of pro-inflammatory cytokine expression in macrophages and macrophage-mediated pro-hypertrophic growth in cardiomyocytes. Results: A hexane fraction of an anti-inflammatory crude extract of American ginseng was found to be most effective in suppressing the inflammatory responses in macrophages. Preparative, reverse-phase HPLC and a comparative analysis by analytical scale LC–UV/MS revealed the hexane fraction contains predominantly C17 polyacetylenes and linolenic acid. Panaxynol, one of the major polyacetylenes, was found to be a potent Nrf2 activator. Panaxynol posttranscriptionally activated Nrf2 by inhibiting Kelch-like ECH-associated protein (Keap) 1-mediated degradation without affecting the binding of Keap1 and Nrf2. Moreover, panaxynol suppressed a selected set of cytokine expression via the activation of Nrf2 while minimally regulating nuclear factor-kappa B (NF-κB)-mediated cytokine expression in macrophages. It also dramatically inhibited the inflamed macrophage-mediated cardiomyocyte death and hypertrophy by activating Nrf2 in macrophages. Conclusions: These results demonstrate that American ginseng-derived panaxynol is a specific Nrf2 activator and panaxynol-activated Nrf2 signaling is at least partly responsible for American ginseng-induced health benefit in the heart. Graphical abstract: Emerging evidence has suggested that regular use of ginseng is helpful for the treatment of cardiovascular diseases; however, the underlying mechanisms are not fully understood. Our results reveal for the first time that panaxynol isolated from American ginseng activates Nrf2-operated anti-inflammatory signaling in inflamed macrophages, thereby suppressing inflamed macrophage-mediated cardiomyocyte death and hypertrophy.